Bangladesh : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria, Extension of the Arrangement, and Rephasing-Staff Report; Staff Statement; Press Release; and Statement by the Executive Director for Bangladesh on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2006)
Bangladesh is reducing poverty and making headway toward meeting its MDGs. However, political considerations are exerting an increasing influence on economic policy decisions. The overall fiscal balance has been kept below budget and program targets, notwithstanding sizable revenue slippages. Monetary policy has been gradually tightened, and the exchange rate has stabilized in recent months, but further monetary tightening is needed. Quantitative performance criteria for the fifth review were met with the exception of that for revenue collection.